Polityka pieniężna Wielkiej Brytanii - Kowalska, Magdalena Maria (Monetary Policy in the United Kingdom, 2007)
The article begins with a brief historical review of monetary relations in United Kingdom and institutional frames of monetary policy today, with a special focus on the Monetary Policy Committee. Subsequently, it presents functional aspects of UK monetary policy shaping, mainly tools, which are given to the Committee in order to aim inflation target set by government. The dispute on the effectiveness of discretional monetary policy and policy based on monetary rules is also presented and applied to the Bank of England practice. The last part of the article contains some remarks regarding to adjustments of British system to European one with the conclusion that the harmonization does take place, however, the intensity of the process is relatively low.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (15); 2007; nr 1166, s. 130-143